Penguatan civic skills siswa melalui ekstrakurikuler Pramuka - Zafira Rahma; Zaky Farid Luthfi; Junaidi Indrawadi; Eni Kurniawati (Journal of Education, Cultural and Politics, 2026)
This study is motivated by the need to strengthen students’ civic skills as an essential foundation for developing active, democratic, and responsible citizens. Scouting (Pramuka) activities are considered to have strong potential as a form of nonformal education that emphasizes experiential learning and social interaction. The purpose of this study is to examine the role of scouting activities in strengthening students’ civic skills at SMP Negeri 1 Sungayang, particularly in terms of situational awareness, decision-making, democratic attitudes, communication, cooperation, and social participation. This research employs a qualitative approach using a case study design. Data were collected through observations, in-depth interviews, and documentation involving students participating in scouting activities, scout leaders, and school administrators. The data were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that scouting activities play a significant role in developing students’ civic skills in a contextual and practical manner. Students demonstrate improved ability to read situations, make collective decisions, communicate effectively, work cooperatively, and participate actively in group activities. Democratic attitudes such as tolerance, respect for differing opinions, and prioritizing group interests are consistently practiced during scouting activities. These results confirm that scouting serves as an effective learning platform for strengthening civic skills through direct experience and social interaction in the school environment.